جماليات التشكيل الثلاثي الأبعاد للخيوط في تصميم الملابس - حسونة، عمرو جمال الدين; حافظ، نشوة مصطفى; أحمد، أسماء رفيع محمد (الجمعية العربية للحضارة والفنون الإسلامية, 2024)
الخامة هي التي تساعد المصمم على توالد أفكاره، فهى الوسيط المادي الذي يساعد المصمم على تحقيق أفكاره بناءًا على الخواص التي تؤثر على أساليب التشكيل. وقد زاد الاهتمام بالتقنيات اليدوية في الوقت الحالي، وتعتبر العُقد من التقنيات الأساسية التي لعبت دورًا مهمًا في الحياة اليومية منذ بدايات التاريخ. وتبرز مشكلة البحث من خلال تساؤلات: ما إمكانية الاستفادة من التشكيل الثلاثي الأبعاد للخيوط في تنفيذ ملابس السيدات باستخدام التقنيات المختلفة للعُقد؟ وما إمكانية الاستفادة من التقنيات المختلفة للعُقد لإثراء القيم الجمالية لملابس السيدات؟ ويهدف البحث إلى توظيف الخيوط في تصميم ملابس السيدات باستخدام تقنيات العُقد، وتنفيذ ملابس سيدات تساير اتجاهات الموضة العالمية باستخدام التشكيل الثلاثي الأبعاد للخيوط، وتتضح أهمية البحث في إلقاء الضوء على الخيوط كخامة ابتكارية يمكن استخدامها لإحياء بعض التقنيات اليدوية، والإستفادة من دمج التقنيات المختلفة للعُقد في إثراء الشكل البنائي للملبس. يتبع البحث المنهج الوصفي التحليلي والمنهج التجريبي. قامت الباحثة بتنفيذ 10 قطع ملبسية باستخدام التشكيل الثلاثي الأبعاد للخيوط من خلال تقنيات العُقد. ولتقييم القطع المنفذة في تحقيق هدف البحث تم إعداد مقياس تقدير (استبانة) موجه للسادة المتخصصين بمجال الملابس. وبعمل التحليلات الإحصائية أظهرت النتائج أن القطعة المنفذة العاشرة حققت أعلى نسبة متوسط حسابي، بينما حققت القطعة المنفذة الثانية أقل نسبة متوسط حسابي. The material is what helps the designer to generate his ideas, as it is the physical mediator that helps him to achieve his ideas based on the properties that affect the methods of modelling. At the present time, the interest of handcraft techniques has increased, The knots are one of the basic techniques which played an important role in everyday life since the beginnings of history, The research problem arises through questions: what is the possibility of benefiting from threedimensional modelling of yarns in the implementation of women's clothing by using knots techniques? What is the possibility of benefiting from knots techniques to enrich the aesthetic values of women's clothing?. The research aims to employ yarns in women's clothing design by using knots techniques and implementation of women's clothes by using three-dimensional modelling and keep up with fashion trends. The research importance is due to highlighting the yarns as an innovative material that can be used to revive handcraft techniques, and benefiting from incorporating different techniques of knots in enriching the structural shape of the garment. The research follows the descriptive analytical method and the experimental method. The researcher implemented 10 pieces of clothing using three-dimensional modelling of yarns through knots techniques. As an assessment to the designs' ability, one questionnaire has been created dressed to specialists in apparel field, The results of the statistical analyses show that deign no. 10 achieved the highest percentage of the arithmetic average, and design no. 2 achieved the least arithmetic average.
Keywords: فن التشكيل بالعقد -- تصميم الملابس -- التقنيات اليدوية -- خامات الخيوط